SISTEMA ÚNICO DE SAÚDE: DO PROTAGONISMO AOS DESAFIOS ATUAIS - de Macedo Rocha, Daniel; Ítalo Arão, Ítalo Arão; Moura de Abreu, Ingrid; Barbosa Ramos, Iara (Revista Enfermagem Atual In Derme, 2024)
Editorial